The use of virtual and augmented reality in science and math education in Arab countries: A survey of previous research studies - Abutayeh, Khaled A.; Kraishan, Osamah M.; Kraishan, Eman Q. (Frontiers in Education, 2022)
The aim of this study was to present a survey of research relating to the use of virtual and augmented reality in science and math education in Arab countries after 2012. The research studies were collected from several sources that include a set of common Arabic research database, a set of English research database, and popular search engines. Thirty three research studies were found related to the use of virtual and augmented reality in science and math education in Arab countries. These studies were examined based on four variables: focus, research method, data collection tools, and geographical distribution. The results showed that most of the research related to uses of virtual and augmented reality in science and math education in Arab countries focused on students and their teachers and most of the researches followed the two-group experimental design, and the quantitative descriptive research. Regarding the methods of data collection most of the studies used test and questionnaires. In addition, most of the research studies were conducted in Saudi Arabia and Egypt. Based on the findings, a set of recommendations were presented.